Subversión femenina en una época pre feminista: análisis de la serie de televisión “Anne with an e” - Picardo Barrientos, Camila Andrea (2020)
This research discusses the female representation and female empowerment discourse in the television series “Anne with an E” revealing the wide range of gender issues it tackles. The methodology employed here examines the narrative and female characters through a sample of episodes, classifying the results within a set of criteria based on gender theory. It was found that female characters became progressively subversive when they had to face the limitations of conventional femininity, developing empowerment through sorority, facilitator characters and the awareness of gender discrimination. However, a contradiction was found within the representation of female racial diversity. In conclusion, female representation in “Anne with an E” is essentially subversive and innovative, with a protagonist that becomes a paradigm of feminist heroism. The show gives visibility to gender issues women faced in the late 19th century turning into a “redemption” from its literary homonymous characters and at the same time achieving to show relevance with present day issues.